Reaksi Pasar Terhadap Peristiwa Politik Terkait Jokowi di Bursa Efek Indonesia - Anis Sundiyah; I Made Sudana (Forum Manajemen Indonesia (FMI), 2015)
This research examines stock market reaction to the political events related of Jokowi in the Indonesia Stock Exchange. Variables used in this research are average abnormal return (AAR) and cumulative average abnormal return (CAAR) which measured using a statistical test one sample t-test. In this research, there are 230 sampel in the announcement Jokowi as a presidential candidate, 316 sampelin the announcement of results of presidential election quick count and 339 sampel in the announcement of work cabinet. Analysis model in this research is event study during the test period of 11 days exchange trading. Consistency of the stock market reaction was compared descriptively based on the analysis of AAR and CAAR. Testresults of AAR and CAAR showed that stock market consistently reacted positively to the announcement Jokowi as a presidential candidate and the announcement of the work cabinet and inconsistent with the announcement of the results of quick count because stock market reacted negatively. keywords: event study, political events of Jokowi, AAR, CAAR, consistency reaction.